AS CONDIÇÕES DE EXPLORAÇÃO DA FORÇA DE TRABALHO NO BRASIL NA FASE ATUAL DO CAPITALISMO: uma análise do período 1990-2007 - Araujo, Elizeu Serra de (2011)
Since the 1990‟s, Brazilian economy, like other dependent economies, has undergone broad changes as part of the reaction to the capital structural crisis started in the mid-1970‟s. Aiming at the restoration of accumulation conditions, these changes have focused on the recovery of the profit rate and the creation of new spaces of capital valorization. The purpose of this study is to analyze how these changes have affected the conditions of exploitation of the labor force in Brazil, taking into account their condition of dependent economy. For that purpose, after describing the theoretical foundations of capitalist exploitation, we placed the issue of exploitation in the specific context of the current phase of capitalism, taking as reference the advanced economies. Then, we discussed the specificities of exploitation of the labor force in the case of dependent economies. Finally, we performed an empirical estimate of the rate of surplus value and the survey of some indication of the leading modes of exploitation in the period, and tried to identify the main determinants of the behavior of these variables. On the one hand, there was a persistent increase in degree of exploitation (except for the underperiod 2005-2007). This increase is due to extension of the depressive phase of world capitalism, which has put on a higher level the contradiction between production and appropriation of surplus value, and the deepening of dependency of Brazilian economy, which resulted in an intensifying of the volume of transfers of value to advanced capitalist economies. On the other hand, this increase in degree of exploitation is associated with maintenance of regressive forms of exploitation of labor power. The classic mechanism of relative surplus value, although also present in the period, still does not present the weight that usually has in advanced economies in terms of contribution to the increase in the rate of surplus value.